Eeg-Derived Estimators of Present and Future Cognitive Performance - Stikic, Maja; Johnson, Robin R.; Levendowski, Daniel J.; Popovic, Djordje P.; Olmstead, Richard E.; Berka, Chris (Frontiers in Human Neuroscience, 2011)
Previous EEG-based fatigue-related research primarily focused on the association between concurrent cognitive performance and time-locked physiology. The goal of this study was to investigate the capability of EEG to assess the impact of fatigue on both present and future cognitive performance during a 20min sustained attention task, the 3-Choice Active Vigilance Task (3CVT), that requires subjects to discriminate one primary target from two secondary non-target geometric shapes. The current study demonstrated the ability of EEG to estimate not only present, but also future cognitive performance, utilizing a single, combined reaction time and accuracy performance metric. The correlations between observed and estimated performance, for both present and future performance, were strong (up to 0.89 and 0.79, respectively). The models were able to consistently estimate “unacceptable” performance throughout the entire 3CVT, i.e., excessively missed responses and/or slow reaction times, while acceptable performance was recognized less accurately later in the task. The developed models were trained on a relatively large dataset (n=50 subjects) to increase stability. Cross-validation results suggested the models were not over-fitted. This study indicates that EEG can be used to predict gross-performance degradations 5 to 15min in advance.